2020
DOI: 10.3389/fnins.2020.557416
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Epileptiform Activity in Cognitive Disorders: Possibilities for a Novel Therapeutic Approach

Abstract: Cognitive impairment is a common and seriously debilitating symptom of various mental and neurological disorders including autism, attention deficit hyperactivity disorder, multiple sclerosis, epilepsy, and neurodegenerative diseases, like Alzheimer's disease. In these conditions, high prevalence of epileptiform activity emerges as a common pathophysiological hallmark. Growing body of evidence suggests that this discrete but abnormal activity might have a long-term negative impact on cognitive performance due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 219 publications
(294 reference statements)
1
21
0
Order By: Relevance
“…[6] Newer AEDs have more selective targets modulating excitability in discreet neuronal circuits and are better positioned for the potential treatment of interictal epileptiform discharges associated with cognitive impairment. [28] The finding from the present study revealed that LEV performed better on assessing memory domain and overall global cognitive function. This is in tandem with many animal and clinical studies showing the cognitive enhancing effect of LEV, a function it was initially developed for from Piracetam.…”
Section: Cognitive Screening Instrument For Dementiasupporting
confidence: 54%
See 1 more Smart Citation
“…[6] Newer AEDs have more selective targets modulating excitability in discreet neuronal circuits and are better positioned for the potential treatment of interictal epileptiform discharges associated with cognitive impairment. [28] The finding from the present study revealed that LEV performed better on assessing memory domain and overall global cognitive function. This is in tandem with many animal and clinical studies showing the cognitive enhancing effect of LEV, a function it was initially developed for from Piracetam.…”
Section: Cognitive Screening Instrument For Dementiasupporting
confidence: 54%
“…An unexplored therapeutic potential in treating cognitive disorders might be the modulation of epileptiform discharges and neuronal excitability. [28] Therefore, it is reasonable to consider the role of AEDs in controlling neuronal toxicity and epileptiform discharges associated with cognitive impairment.…”
Section: Annals Of Health Research Volume 7 Issue No 2 2021_________________________174mentioning
confidence: 99%
“…Novel observations started to draw more attention to SEA since increased incidence is detected consistently in diseases affecting cognitive functions, including AD ( 42 ). Based on recent reviews, the leading research sites agree that SEA is a characteristic EEG hallmark of AD-related cortical hyperexcitability ( 10 , 42 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Novel observations started to draw more attention to SEA since increased incidence is detected consistently in diseases affecting cognitive functions, including AD ( 42 ). Based on recent reviews, the leading research sites agree that SEA is a characteristic EEG hallmark of AD-related cortical hyperexcitability ( 10 , 42 45 ). It seems also feasible that the imbalance between excitatory and inhibitory regulation propagates from the dentate gyrus to the hippocampus and later to cortical structures explaining the dominant occurrence of SEA in the temporal regions ( 43 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation